Phase equilibria study of the ZnO–'FeO'–SiO2–MgO system at Po2 10−8 atm. Issue 4 (2nd October 2018) - Liu, Hongquan; Cui, Zhixiang; Chen, Mao; Zhao, Baojun
ABSTRACT: Experimental studies on the liquidus temperature and phase relations of the ZnO–'FeO'–SiO2 –MgO system have been investigated at Po2 10 −8 atm related to the copper smelting slag. The experimental technique applied in present study involves master slag preparation, high-temperature equilibration, quenching and EPMA analysis. The impact of MgO content on the liquidus temperature and partitioning behaviour of ZnO has been evaluated. It was found that the presence of MgO content in the slag can significantly increase liquidus temperature in spinel primary phase field and narrow the full liquid area at a given operating temperature. The ZnO and MgO concentrations in the liquid phase are higher than those in the spinel phase. The present study provides more accurate information for copper smelting slags and optimisation of the thermodynamic modelling.